Pengaruh Frekuensi Konsumsi Kopi Terhadap Kadar Asam Urat, Glukosa Dan Tekanan Darah Pada Tenaga Kependidikan UNDANA - Conrad Folamauk (Universitas Nusa Cendana, 2026)
The increase in the burden of non-communicable diseases is in line with the increase in risk factors, including the eating and drinking patterns of the people themselves. Coffee is one of the most popular drinks in Indonesian society. The effect of coffee on blood pressure will impact public health. Coffee containing caffeine can stimulate the heart to work faster, flowing more fluids every second. The habit of drinking coffee is obtained from one cup containing 75–200 mg of caffeine. Drinking more than four cups of coffee can increase systolic blood pressure by around ten mmHg and diastolic blood pressure by around eight mmHg. This study aims to determine the effect of the frequency of coffee consumption on uric acid levels, glucose, and blood pressure among employees at UNDANA. This study uses a case-control research design. The research samples were Rectorate employees and 3 Faculties at UNDANA who met the inclusion and exclusion criteria. The sampling technique used is Volunteer sampling. The results showed that 52% of employees consumed coffee 1-2 times daily. The frequency of coffee consumption affects cholesterol levels, blood glucose levels, and systolic and diastolic blood pressure among employees at the University of Nusa Cendana.